Multiphase adjuvant neuroprotection: A novel paradigm for improving acute ischemic stroke outcomes - Zhao, Wenbo; Wu, Chuanjie; Dornbos III, David; Li, Sijie; Song, Haiqing; Wang, Yuping; Ding, Yuchuan; Ji, Xunming (Brain circulation, 2020)
While several large pivotal clinical trials recently revealed a substantial benefit of endovascular thrombectomy for acute ischemic stroke (AIS) caused by large-vessel occlusion, many patients still experience mediocre prognosis. Enlargement of the ischemic core, failed revascularization, incomplete reperfusion, distal embolization, and secondary reperfusion injury substantially impact the salvaging of brain tissue and the functional outcomes of AIS. Here, we propose novel concept of "Multiphase Adjuvant Neuroprotection" as a new paradigm that may help guide our search for adjunctive treatments to be used together with thrombectomy. The premise of multiphase adjuvant neuroprotection is based on the diverse and potentially nonoverlapping pathophysiologic mechanisms that are triggered before, during, and after thrombectomy therapies. Before thrombectomy, strategies should focus on preventing the growth of the ischemic core; during thrombectomy, improving recanalization while reducing distal embolization and maximizing reperfusion are of significant importance; after reperfusion, strategies should focus on seeking targets to reduce secondary reperfusion injury. The concept of multiphase adjuvant neuroprotection, wherein different strategies are employed throughout the various phases of clinical care, might provide a paradigm to minimize the final infarct size and improve functional outcome in AIS patients treated with thrombectomy. With the success of thrombectomy in selected AIS patients, there is now an opportunity to revisit stroke neuroprotection. Notably, if the underlying mechanisms of these neuroprotective strategies are identified, their role in the distinct phases will provide further avenues to improve patient outcomes of AIS.